Antiviral Potential of Patikan Kebo Extract against Chicken Corona Virus through In Ovo Challenge Test - Sufahmi Anggraheni; Nurul Humaidah; Freih Jailani; Nadiah Nurhaliza; Risky Rahmad Indarto (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2023)
The coronavirus, known to exist in humans and livestock for an extended period, includes variants such as the infectious bronchitis (IB) virus in chickens. As a single-stranded RNA virus, coronaviruses are prone to mutations. Patikan Kebo (Euphorbia hirta L) is a medicinal herb containing various compounds like Flavonoids, Mirisil, Alkaloids, Laraserol, Hentriakontanol, and Komositin, known for their antibacterial, antiviral, and anti-worm properties. This study aimed to evaluate the toxicity of Patikan Kebo extract on Chicken Embryo Eggs (TAB) and assess its antiviral potential against the chicken AI coronavirus. The experimental approach involved three concentrations of Patikan Kebo extract (0.01% - P1, 0.1% - P2, 1% - P3), a control group without Patikan Kebo extract (K+), and a control group without the virus (K-). Data analysis was conducted using ANOVA and Tukey HSD in the SPSS program. The results from ANOVA indicated that the dose of Patikan Kebo significantly impacted (P<0.05) its antiviral activity against the IB virus. The average HA Titer 2 (Log2) demonstrated a 47% reduction in viral activity. In conclusion, the most effective herbal antiviral dose against the IB virus was determined to be 0.1% Patikan Kebo extract.